Serum iron level and methemoglobin concentration among women with gestational diabetes - Adedeji David Atere; Cinderella Ebele Chukwuemeka; Olayiwola Akanji Popoola; Temiloluwa Deborah Olawoye (Biomedical and Biotechnology Research Journal, 2022)
Background: Gestational diabetes mellitus(GDM) is carbohydrate intolerance that causes hyperglycemia in pregnancy. It increases maternal and perinatal mortality. This study aims to determine the relationship between gestational diabetes and plasma iron and methemoglobin levels. Methods: The study included 40 GDM patients, 30 nongestational diabetes pregnant women (NGPW) attending the antenatal clinic of Federal Medical Centre, Owo, and 30 women with neither diabetes nor pregnancy (NDNP). Ten milliliters of venous blood was collected from each individual and dispensed into an appropriate bottle. Fasting blood sugar (FBS), serum level of iron (Fe2+), methemoglobin (MetHb) concentration, and packed cell volume (PCV) were determined using standard laboratory techniques. The data were properly analyzed statistically, and P < 0.05 was considered statistically significant. Results: The mean value of MetHb and Fe2+ was significantly higher among GDM and NGPW when compared with NDNP (P < 0.05) while the mean value of PCV was considerably lower (P < 0.05). Furthermore, there was a significant positive correlation between FBS and PCV in GDM, while FBS had a negative correlation with only Fe2+ in GDM. Conclusion: It was concluded that elevated serum iron levels and MetHb were found to be associated with the development of GDM in this study, and could thus be used as biomarkers for assessment.